Microglia in Multiple Sclerosis: Friend or Foe? - Guerrero, Brooke L.; Sicotte, Nancy L. (Frontiers in Immunology, 2020)
Microglia originate from myeloid progenitors in the embryonic yolk sac and play an integral role in central nervous system (CNS) development, immune surveillance and repair. The role of microglia in multiple sclerosis (MS) has been complex and controversial, with evidence suggesting that these cells play key roles in both active inflammation and remyelination. Here we will review the most recent histological classification of MS lesions as well as the evidence supporting both inflammatory and reparative functions of these cells. We will also review how microglia may yield new biomarkers for MS activity and serve as a potential target for therapy.